(untitled) (Research, Society and Development, 2020)
This article proposes a reflection on the process of teacher training in the conception of Ildeu Coêlho. Approaching teacher training is relevant, since, in the existence of collective life, in the educator’s ideas and pedagogical practices, the search for equality and social justice must be intertwined. To this end, we conducted a literature review and bibliographic research on Ildeu Coêlho’s manuscripts to analyze the main concepts that constitute his intellectual production. In this way, we discuss the historicity and contradiction of teacher training, as well as the teacher training process in promoting autonomy in the light of Ildeu Coêlho’s thought. The results achieved by this research reveal that for such a complex issue, it would be impossible to present proposals for simplistic solutions or even closed conclusions. Therefore, we reaffirm the need to reflect philosophically, considering the possibilities and contradictions that exist in the process of teacher training, since we perceive an impoverishment of the understanding of education, school, cultural and human formation, in recent times. Therefore, it is necessary to persist in the search for new educational and teaching, learning and teacher training concepts and practices, which are aligned with the humanization of all human beings, committed to the promotion of truth, equality and justice.